Mathematical model for reactive recovery of invertase by chemical permeabilization of baker's yeast - Koli, Aditya C; Subhedar, Preeti B; Pamidipati, Sirisha; Gaikar, Vilas G (Journal of chemical technology and biotechnology (1986), 2016)
BACKGROUND: Cell permeabilization techniques allow selective release of an enzyme and specific reactions without breaking the cells. A mathematical model has been developed for selective permeabilization of Saccharomyces cerevisiae to recover invertase at high purity. The effect of thiols on the cell walls of S. cerevisiae was studied under different conditions of pH, cysteine concentration, speed of agitation and solid suspension density. RESULT: The rate of release of invertase was a function of pH and cysteine (or thiolate ion) concentration. The maximum recovery of invertase was obtained at pH 10.0, 10 mmol dm⁻³ cysteine concentration and 15% (w/v) yeast loading. CONCLUSION: Thiols are capable of permeabilizing the cell walls of S. cerevisiae and releasing the invertase under basic conditions. The insignificant effect of agitation shows that the external mass transfer resistance does not play any role in the release of invertase. © 2015 Society of Chemical Industry